2021
DOI: 10.3390/diagnostics11091523
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Radiomics and Deep Learning for Nasopharyngeal Carcinoma Imaging

Abstract: Nasopharyngeal carcinoma (NPC) is one of the most common malignant tumours of the head and neck, and improving the efficiency of its diagnosis and treatment strategies is an important goal. With the development of the combination of artificial intelligence (AI) technology and medical imaging in recent years, an increasing number of studies have been conducted on image analysis of NPC using AI tools, especially radiomics and artificial neural network methods. In this review, we present a comprehensive overview … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 178 publications
(217 reference statements)
0
36
0
1
Order By: Relevance
“…Radiomics models based on MRI features in nasopharyngeal carcinoma (NPC) can predict the prognosis and therapeutic responses [28], but these models were constructed based on basic MR sequences (e.g., T2WI, T1WI, and CE-T1WI). Studies with a radiomics approach based on DWI images in nasopharyngeal carcinoma remain to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics models based on MRI features in nasopharyngeal carcinoma (NPC) can predict the prognosis and therapeutic responses [28], but these models were constructed based on basic MR sequences (e.g., T2WI, T1WI, and CE-T1WI). Studies with a radiomics approach based on DWI images in nasopharyngeal carcinoma remain to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Our study had some limitations, predominantly in terms of methodology. This was a retrospective study with a moderate number of patients (124) (reported sample sizes in the literature range from 85-737 [3]), with mixed clinical stages of NPC (I-IV). Other prognostic molecular biomarkers, such as Haemoglobin, LDH, neutrophil-lymphocyte ration, c-Met, ERBB3 and MTDH were not available for inclusion in the study [21], as these were not routinely obtained at this time at our institute.…”
Section: Limitationsmentioning
confidence: 99%
“…NPC affects less than 1 person per 100 000 in North America [2], however is endemic in Southern China, the Middle East and North Africa [2]. Although the prognosis of NPC is largely good, with 5 year survival rates reaching up to 80% [3], 20-30% of patients experience treatment failure from locoregional recurrence or distant metastasis [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these early reports either mainly focused on advanced NPC [ 11 ], or only predicted local-regional recurrence without metastasis in some studies [ 12 , 13 ], or just focused on distant metastasis [ 5 ]. The same as radiomics, deep learning (DL) has also become one of the most important artificial intelligence (AI) tools, whose application in NPC have been gradually increasing since 2017 [ 14 ]. Jing [ 15 ] established an end-to-end multi-modality deep survival network (MDSN) to predict the risk of disease progression of NPC patients, but the best performance was a C-index of 0.651.…”
Section: Introductionmentioning
confidence: 99%